iMasjid: mobile application for Muslims / Tuan Muhammad Hanif Tuan Hassan - Tuan Hassan, Tuan Muhammad Hanif (2020)
Muslims are having problem in finding mosque’s teaching schedule information as there are no centralize platform for this kind of information. Muslims need to go to the mosque in order to obtain the schedule as the timetable that usually being advertise weekly. Besides, people also lack of time to attend the Islamic teaching class organized by the Mosque’s committee. This issue will lead to lack of Islamic knowledge in the Muslims society. This project purpose is to create a mobile system application with a notification features named iMASJID. iMASJID will list out a number of mosques and muslims can obtain the Islamic teaching class schedule for mosque that are near to them. Besides, users may set an alarm for the upcoming classes. This iMASJID application will be available to the android based mobile device users as it is being developed using the Android Studio. The development of the mobile apps need a PC with software of Android Studio and Flutter installed. For the hardware, the requirements are 4 Gigabit RAM and 4 Gigabit of available storage. I had used HP ProBook 640 laptop that powered by Intel Core i5, 12 Gigabit of RAM and 128 Gigabit SSD. The users need to have internet connectivity in order to use this application tin order to obtain data from the server. The iMASJID application has been developed successfully and is hoped will be very helpful to aid muslims in getting Islamic knowledge that will lead them to a better lifestyle.